Biopolitics of Knowledgeable Neglect: The Case of Famine in Kazakhstan in 1931-1933 - Peleo, Aliya Sartbayeva (Jurnal Hubungan Internasional, 2018)
This article examines and problematizes the historic case of famine in Kazakhstan in 1931-33 to illustrate that ‘starvation’, ‘famine,’ or ‘food crisis’ occurred primarily because of ‘knowledgeable neglect’ by the Soviet governance system in order to pursue the priorities of modern development, such as industrialization in the context of overall social modernization of population. The paper also explores the concepts of ‘famine’ through Malthusianism, ‘entitlement approach’ and ‘new famine’. It also explains the biopolitical implications of these concepts using the historical case of the 1931-1933 famine in Kazakhstan. The case shows that particular Soviet government policies and political decisions by individual officials to worsened the condition of marginalized communities at the social periphery for the attainment of a ‘greater good’ of the government national priorities, particularly overall industrialization and modern economic development. The case demonstrates that any promotion of a dominant ‘identity’, particularly in its modernist form with ‘civilizing’ function, exposes the inclination towards exclusion and repression of ‘bare life’ of marginalized people at the periphery. On the whole, the article critically explores the ‘famine’ as a complex biopolitical problem of public action or inaction, failure of accountability, and therefore ‘knowledgeable neglect’ of periphery populations.